Variation in Anatomical Structure of Teak and its Influence on Specific Gravity and Maximum Crushing Stress - Purkayastha, S. K.; Tandon, R. D.; Ramesh Rao, K. (Indian Forester, 1972)
Anatomical studies of some tested samples of teak from seven different localities have shown that fibre wall thickness is highly correlated with specific gravity. This relationship is influenced to some extent by the proportion of fibres. Highly significant correlation has also been found to exist between fibre wall thickness and maximum crushing stress in the samples in which the wall thickness is less than 4Î¼.